The impact of inventory management and supply chain on the performance of industrial enterprises: A case study of TAYAL SPA - Elhabib, Mekkaoui; Abderrahim, Belaidi; Rayen, Rekmouche (International journal of economic perspectives, 2024)
In the current economic background, inventory and supply management is critical to maintain the competitiveness of industrial firms. Effective management makes it possible to respond quickly to customer needs while minimizing the costs linked with purchasing, storing and moving products. However, errors in these processes can lead to delays and additional costs. The study conducted on the company TAYAL SPA demonstrates that optimizing inventory and supply management promotes customer satisfaction, improves economic performance and increases profitability. The results highlight the importance of adopting effective logistics strategies to maintain a strong competitive position in the global market.